The Influence of the TPS Type Cooperative Learning Model Assisted by Integrated PPT Media on High School Students' Collaboration Skills - Mahmudyah, Niken Noviana; Mahardika, I Ketut; Subiki, Subiki (Peneliti.net, 2025)
21st century skills are important for schools as educational institutions. One of the 21st century skills that can be developed and achieved by students in learning activities is collaboration skills. Collaboration skills are very important in learning at school, one of which is in physics learning. Collaboration skills can be achieved with learning models and media used in the learning process. However, not all learning processes can improve students' collaboration skills. This study aims to examine the effect of the TPS type cooperative learning model assisted by integrated PPT media on the collaboration skills of high school students. This research method uses True Experimental with a Posttest Only Control Group Design design consisting of an experimental class treated with the TPS type cooperative learning model assisted by integrated PPT and a control class using the Problem Based Learning (PBL) learning model. The sampling of this study used the cluster random sampling technique and if after the Levene's test the data was not homogeneous, then the value between classes with the smallest difference was used. Analysis of the research data used SPSS 25 with a normality test, and an independent sample t-test hypothesis test if the data was normal or a Mann Whitney U test if the data was not normal. The results of the study showed that collaboration skills with an Asymp value. Sig. (2-tailed) of 0.045, which means there is a difference between the experimental class and the control class. So it can be concluded that the TPS type cooperative learning model assisted by integrated PPT media has a significant effect on the collaboration skills of high school students.